INNOVATIVE APPROACHES TO PRESCHOOL EDUCATION AND MODELING TECHNOLOGIES - Khaydarova Zulfiya Orifjonovna (Web of Journals Publishing, 2024)
This article discusses the reforms implemented in the preschool education system in Uzbekistan in recent years, the positive results achieved in the field of preschool education and their impact on the transition to the digital economy, the advantages of multimedia and modeling educational technologies.
Keywords: development, preschool education, inclusion in education, multimedia, technology, modeling, mathematical imagination, sensory abilities.